Foliar trichomes of Croton L. (Euphorbiaceae: Crotonoideae) from China and its taxonomic implications - Liu, Huan-Fang; Deng, Yun-Fei; Liao, Jing-Ping (Bangladesh Journal of Plant Taxonomy, 2013)
Foliar trichomes of 21 species of the genus Croton L. from China have been examined using stereomicroscopy and scanning electron microscopy. Five trichome types characterized by their morphology are identified, viz., stellate, lepidote, simple, dendritic and appressed-rosulate. Only stellate trichome is observed in most species, with only six species that are found to maintain two or three trichome types. Trichome types and density are useful for species identification and sectional classification for Chinese species. Based on the trichome types and other morphological characters, 21 Chinese species are proposed to be placed in five sections. Croton crassifolius belongs to sect. Andrichnia; C. cascarilloides belongs to sect. Monguia; C. mangelong, C. kongensis, C. laevigatus and C. laniflorus belong to sect. Argyrocroton; C. lauioides, C. howii and C. damayeshu belong to sect. Adenophylli. The remaining Chinese Croton species might be placed into sect. Croton. A key for Chinese Croton species based on trichome morphology is provided. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15468 Bangladesh J. Plant Taxon. 20(1): 85-94, 2013 (June)